BREAST ULTRASOUND IMAGE ENHANCEMENT TECHNIQUES FOR CANCER DETECTION AND CLASSIFICATION - Silva, Daniel Santos da (2023)
SILVA, Daniel Santos da. Breast ultrasound image enhancement techniques for cancer detection and classification. 2023. 83f. Dissertação (Mestrado em Engenharia de Teleinformática) - Centro de Tecnologia, Universidade Federal do Ceará, Fortaleza, 2023.